An Analysis of the Lexical Density and Readibility of Reading Materials in - Untsa Rohmah Fadzillah (Universitas Ahmad Dahlan, 2022)
This research aims to find out the lexical density levels of the reading texts in the English for Institutional Course (EFIC) textbook, determine the readability levels of the texts, ascertain the level of appropriateness of the texts for EFL undergraduate students, and determine the suitability of the textbook for the students based on its lexical density and readability. This research used the theory from Nunan (as cited in Ramadhan, Santihastuti, & Wahjuningsih, 2017) for the lexical density and the theory from Verderber, Sellnow, and Verderber (2017) for the readability. It applied quantitative method and utilized the lexical density and readability formulas from by Ure and Flesh Readin